Indoor secondhand tobacco smoke emission levels in six Lebanese cities. Issue 2 (8th April 2010) - Saade, Georges; Seidenberg, Andrew B; Rees, Vaughan W; Otrock, Zaher; Connolly, Gregory N
Abstract : Background: To date, Lebanon has failed to enact comprehensive clean indoor air laws despite ratification of the Framework Convention on Tobacco Control (FCTC), which calls for the protection of non-smokers from exposure to secondhand tobacco smoke (SHS). Complicating the problem of SHS exposure in Lebanon is the widespread use of the tobacco water-pipe. While most research on SHS has involved cigarette smoking as a source of emissions, other sources, including tobacco water-pipes, may be an important contributor. Methods: PM2.5 concentrations (μg/m 3 ) were measured in a sample of 28 public venues located in six major Lebanese cities. Active smoker density (number of smokers/100 m 3 ) was calculated for both water-pipe and cigarette smokers. Venues were then categorised as having higher density of water-pipe smokers or higher density of cigarette smokers, and resultant emission levels were compared between the two groups. Results: Cigarette and water-pipe smoking was observed in 14 venues, while cigarette smoking only and water-pipe smoking only were found in 12 venues and one venue, respectively. Among all smoking-permitted venues, the mean PM2.5 concentration was 342 μg/m 3 . Venues with a higher density of water-pipe smokers (n =14) showed a similar median PM2.5 concentration (349 μg/m 3 ) compared with venues with a higher density of cigarette smokers (n =13; 241 μg/m 3 ; p=0.159). The mean PM2.5 concentration in the single venue with a voluntary smoke-free policy was 6 μg/m 3 . Conclusions: Despite ratification of the FCTC in 2005, both cigarette and water-pipe smoking are commonly practised in enclosed public places throughout Lebanon, leading to unsafe levels of indoor particulate pollution. Smoke-free policies are needed in Lebanon to protect the public's health, and should apply to all forms of tobacco smoking.